Effects of varied music applications in cycle ergometry - Lim Ban Tec, H. (2012)
The aim of this research programme was to investigate the effects of different music applications: The differentiated exposure of music and the synchronous application of music. In Study 1, participants completed a series of 10-km cycling time trials under four single-blinded conditions: No-music control, music 0-10 km (M1), music 0-5 km (M2), and music 5-10 km (M3). The largest performance gains were noticed under M1, followed by M3, when compared to control, while the most positive psychological response was observed only in M3. Study 2 further examined the notion of differentiated music exposure by incorporating both quantitative and qualitative modes of inquiry. In addition, participants were given foreknowledge of the experimental conditions. Although no performance gains were found across conditions, M3 significantly reduced perceived exertion and prevented affective decline. Qualitative findings suggest that prolonged exposure to music may have negative psychological and psychophysical consequences. The last study contrasted the effects of synchronous and asynchronous application of music in a 6-min submaximal cycling task. Synchronous music was more effective than asynchronous music in terms of reducing perceptions of exertion and increasing subjective arousal. Although no changes in oxygen uptake were found across conditions, auditory-motor synchronisation appeared to reduce heart rate. The contribution of this thesis is twofold. Firstly, the provision of music in the latter stages of a task appears to have significant psychological and psychophysical benefits when compared against constant music exposure. Secondly, more positive effects, in terms of perceived exertion and subjective arousal, are observed when music is applied synchronously compared to asynchronously; this suggests a need for a separate conceptual framework for the application of synchronous music